Women in otorhinolaryngology: a historical perspective. Issue 8 (23rd July 2018) - Konstantinidou, S; Adams, M
Abstract: Background: Otorhinolaryngology has an extensive history that spans nearly five millennia, and the history of women as medical and surgical practitioners stretches back to at least 3500 BC. Objectives: To explore the history of women in ENT from ancient to modern times, and discover their fascinating role in this field over the years. Method: A literature review was conducted using Google Scholar and PubMed. Results: In ancient and medieval times, there were female doctors accomplished in areas pertaining to ENT. In the nineteenth and twentieth centuries, inspirational women pioneers paved the way for modern female ENT surgeons. This led to a rapid increase in the representation of female otorhinolaryngologists in clinical practice and authorship over the last fifty years. Conclusion: The contribution of women to otorhinolaryngology has evolved since ancient times and the greatest advancement has occurred within the last two hundred years.